Long-term surgical outcomes of esotropic duane retraction syndrome type 1 - Jihae Park; Hee Kyung Yang; Jeong-Min Hwang (Scientific Reports)
Abstract Duane retraction syndrome (DRS) is complicated to treat due to its wide spectrum of clinical presentations and the treatment of choice varies among surgeons. To provide insight into this challenging condition, we evaluated the long-term surgical outcomes of esotropic DRS type 1. The surgical motor success, defined as a horizontal deviation of 8 prism diopters (PD) or less, was found in 77.3% of patients after an average follow-up of 5.6 ± 3.4 years. After surgery, a gradual shift towards exotropia was observed at an average rate of 1.3 ± 3.7 PD exodrift per year. In this study, the long-term surgical outcomes were generally favorable in esotropic DRS type 1. However, due to the nature of exodrift over time following medial rectus recession, it is crucial to educate the patient about the potential long-term overcorrection, and to carefully calculate the appropriate surgical dosage.